Inguinal Hernia Repair - Vitorino Modesto dos Santos; Lister Arruda Modesto dos Santos (Journal of Surgery and Surgical Research - Peertechz Publications, 2017)
Inguinal hernia is a common condition with great number of referrals from primary health care to general surgeons, and the treatment is corrective surgery in practically all cases [1,2]. The options include open or laparoscopic approaches, absorbable or non-absorbable meshes, and the major complications have been the local chronic pain and the recurrence of hernia [1]. These main concerns about complications of open hernia repair are related to inadequate mesh dimension or position, and foreign body inflammatory reaction to material of the meshes [1]. Moreover, this surgical entity is one of main causes of absenteeism due to health problem [2]. We read with special interest the Research Article done by Simone Metal. about "a new chance for open inguinal hernia repair", which was recently published in this Journal [1]. They retrospectively analyzed data obtained during 18 months from 710 surgical patients; and 85.45% were men with mean age of 51.8% whereas the mean age of women was 62 years [1]. The purpose was to evaluate a partially absorbable (90% poly-L-lactic acid) mesh that can elicit less intense foreign body reaction, with reduced local inflammatory phenomena [1].